GAMBARAN USIA MENARCHE DINI DI PADA ANAK SEKOLAH DASAR DI DAERAH URBAN - Ratna Puspita Sari; Ari Udiyono; Lintang Dian Saraswati; Praba Ginandjar (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Menarche is the first mentrual period by a woman. There a decline in the secular trend of age of menarche in girls The aim of this study was to describe the prevalence of early in private elementary schools students in urban areas. The population of this study were all students in grade IV, V, and VI of elementary schools in Semarang Selatan. 100 samples were chosen by using simple random sampling method. The results showed that the prevalence of early menarche was 20%. Early menarche was mostly found on children with obesity, overweight, and good nutrial status. Early menarche was also mostly found on children with high socioeconomic, had been exposed by audio visual media, less physical activity and high body fat percentage. Parents suggested to watch the uses of the mass media and gadgets in their children.